PENERAPAN MODUL MITIGASI BENCANA YANG TERINTEGRASI DALAM PELAJARAN IPA DI SMP TERDAMPAK TSUNAMI - Al’afani, Fatwa; Wahyono, Unggul; Miftah, Miftah (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2022)
This research was conducted to know the level of effectiveness of implementing an integrated disaster mitigation module in science lessons in SMP affected Tsunami on student learning outcomes. This type of research is a weak experiment with a pre-experimental design. The population of this study was all class VIII SMP.N 10 Palu. The sampling technique used in this study was purposive sampling with the sample of this study being class VIII B as an experimental class with a total of 17 students. The learning outcome instrument is a multiple-choice test that has been validated through an expert validator. The learning outcomes test obtained explained that the average score of the posttest experimental class was 15.82, which was higher than the pretest experimental class, which was 12.24. Testing the t-test hypothesis, obtained count > ttable or 10.23 > 1.74 at the real level = 0.05. This means that the value of count is outside the area of ​​acceptance of H0. So it can be concluded that there is an increase in student learning outcomes in science (physics) towards the application of the integrated disaster mitigation module in science lessons.